1992
DOI: 10.1080/01688639208402847
|View full text |Cite
|
Sign up to set email alerts
|

Verbal and nonverbal skill discrepancies in hydrocephalic children

Abstract: This study evaluated a large sample (N = 90) of 5- to 7-year-old children with hydrocephalus caused by aqueductal stenosis or prematurity-intraventricular hemorrhage or associated with spina bifida. Comparison groups of normal controls, children with spina bifida and no shunt, and premature children with no hydrocephalus were also evaluated. Comparison of skill discrepancies at two occasions separated by 1 year revealed that hydrocephalic children, as a group, showed poorer nonverbal than verbal skills on meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 18 publications
5
61
0
3
Order By: Relevance
“…Shunting does not restore normal CSF circulation, which is important for carrying growth factors and cytokines to neuronal and glial precursor cells in the germinal matrix surrounding the lateral ventricles (Miyan et al, 1998). Children treated with shunts frequently have residual neurological deficits (Fernell et al, 1990(Fernell et al, , 1994Fletcher et al, 1992;McAllister et al, 1998), including impaired memory (Scott et al, 1998). Shunts are also associated with a high risk for complications such as infection, obstruction, and over drainage (Pople et al, 1990;Blount et al, 1993); nearly 70% of shunts require revision within 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Shunting does not restore normal CSF circulation, which is important for carrying growth factors and cytokines to neuronal and glial precursor cells in the germinal matrix surrounding the lateral ventricles (Miyan et al, 1998). Children treated with shunts frequently have residual neurological deficits (Fernell et al, 1990(Fernell et al, , 1994Fletcher et al, 1992;McAllister et al, 1998), including impaired memory (Scott et al, 1998). Shunts are also associated with a high risk for complications such as infection, obstruction, and over drainage (Pople et al, 1990;Blount et al, 1993); nearly 70% of shunts require revision within 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…With improvements in treatment and the use of CSF derivations, the majority of infants with SB and hydrocephalus have normal intelligence, although their IQs are lower than those seen in normal controls [5, 6]. However, hydrocephalus can be associated with various neuropsychological impairments, particularly visuospatial or constructional skills [5, 7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Damage to white matter is thought to be the cause of such defects, and may contribute to impaired development of non-verbal cognitive skills in children with hydrocephalus (Donders et al 1991, Fletcher et al 1992b). There appears to be impairment of the processes linking the structural description of objects to their locations and there may be an improved ability to identify simultaneously presented stimuli when they were thematically related (Coslett and Saffran 1991).…”
Section: Visuospatial Perceptionmentioning
confidence: 99%
“…They felt that these findings were due to more than just ocular or fine motor dysfunction. Other authors have found a discrepancy between verbal and non-verbal cognitive skills (Fletcher et al 1992b). In a MRI study by Fletcher and coworkers (1992a), it was concluded that non-verbal cognitive skill development requires intact white matter in both hemispheres.…”
mentioning
confidence: 97%